Screening of Antimicrobial Activity of Indian Medicinal Plants - S.M. Muthukkaruppan3, Sajani Samuel1*, P.K. Senthilkumar2 and (Journal of Experimental Sciences, 2010)
<div style="border-bottom: medium none; border-left: medium none; padding-bottom: 0in; padding-left: 0in; padding-right: 0in; background: white; border-top: windowtext 1pt solid; border-right: medium none; padding-top: 1pt; mso-element: para-border-div; mso-border-top-alt: solid windowtext .5pt;"> Abstract Crude extracts from seeds viz., Hydnocarpus wightiana, Nyctanthes arbor-tristis, Wrightia tinctoria, Alangium lamarckii and Carum copticum were prepared using the solvents ethanol, methanol, acetone and aqueous. The extracts were screened for their antibacterial activity against four bacterial pathogens and phytochemical analysis were also carried out. The tested bacterial strains were Escherichia coli, Salmonella typhi, Proteus mirabilis and Klebsiella pneumoniae. Among the extracts methanol extract of all the seeds exhibited higher activity followed by ethanol, aqueous and acetone. Among the test organisms Klebsiella pneumoniae and Proteus mirabilis showed higher sensitivity towards all the seed extracts followed by Escherichia coli and Salmonella typhi. Carum copticum was found to be highly effective comparatively to others. The antibacterial potential of the extracts were found to be dose dependent. These activities of the seeds were due to the presence of various secondary metabolites. Â Key words: Antibacterial activity, Bacterial pathogens, Secondary metabolites 1M.Phil., Research scholar, Department of Microbiology, Annamalai University, Annamalainagar â€“608 002, Tamilnadu, India; 2Lecturer, Department of Microbiology, Annamalai University, Annamalainagar-608 002, Tamilnadu, India; 3Professor, Department of Microbiology, Annamalai University, Annamalainagar-608 002, Tamilnadu, India Â Please Cite This Article As: Â Sajani Samuel, P.K. Senthilkumar and S.M. Muthukkaruppan. 2010. Screening of Antimicrobial Activity of Indian Medicinal Plants. J. Exp. Sci. 1(6):25-31.